The development of a Sales Channel Strategy Framework for Lufthansa German Airlines in the Portuguese Market - Reinholz, Julian Marius (2019)
This paper explores the sales channel strategy of a major European passenger airline in the Portuguese market and gives implications to optimize the channel structure. Research was conducted to segment the airline’s customers according to service outputs demanded of each channel, and to further outline potential demand-side gaps and supply-side gaps within the current channel design. Results imply that offering personalized fares that are directly linked to the customers via the airlines corporate website, supports the satisfaction of their needs, reduces costs for the airline and brings with it the possibility to provide them with ancillary products.